A systematic review of preclinical animal studies on fenofibrate’s potential role in type 1 diabetic micro-vascular complications - Varghese, Resia (2023)
Fenofibrate is a peroxisome-proliferator-activator α agonist and it is a widely used drug for hyperlipidemia since its approval in 2004. So, in this review we are focusing on the effect of fenofibric acid’s mechanism to alleviate type 1 diabetic micro vascular complications like diabetic retinopathy, diabetic cardiomyopathy in animal models, since the drug is safe, efficacious and more economical when compared with the currently available treatment strategies for juvenile diabetic complications and also a profound observation is needed due to the rarity of research in these therapeutic areas. Important preclinical animal studies published from January 2001 to June 2020 were recognised from databases like PubMed and Cochrane central register of controlled trials. Reviewers screened the articles based on the selection criteria and risk of bias was determined using Systematic Review Centre for Laboratory animal Experimentation risk of bias tool for animal studies. Our literature search yielded a total of 5 studies and after pooling up the data from the 5 preclinical studies, we found that Fenofibrate have the efficacy to prevent type 1 diabetic complications, chiefly diabetic retinopathy and those mechanisms are dependent on peroxisome-proliferator-activator and fibroblast growth factor-21 pathways. Fenofibrate is a well safe and moreover, cost effective medication in preventing type 1 diabetic micro vascular complications especially diabetic retinopathy and also in maintaining the glucose homeostasis in apart from its anti-dyslipidemic effect.